Keys to go through "Being and Time", by Martin Heidegger - Belmonte García, Olga (Razón y fe, 2018)
In this article we present the fundamental lines of the work «Being and Time», by Martín Heidegger. He is a philosopher who has had a considerable influence on contemporary thought, both due to the criticism he has received and to those who consider him an inspiration for existentialism. Our goal is to make his main work accessible to readers unfamiliar with him and to provoke reflection on the issues he raises. We will make us ask ourselves to what extent the description of existence that he proposes, based on finitude, makes openness to transcendence impossible.